De Backer, Mattias; Melgaço, Lucas; Varna, Georgiana i Menichelli, Francesca (eds.) (2016). Order and conflict in public space - Ortiz Guitart, Anna (Documents d'Anàlisi Geogràfica, 2017)
De Backer, Mattias; Melgaço, Lucas; Varna, Georgiana i Menichelli, Francesca (eds.) (2016) Order and conflict in public space Oxon: Routledge, 227 p. ISBN 978-1-138-93118-3